Analisis Pendapatan Petani Kelapa Di Desa Talawaan Kecamatan Talawaan Kabupaten Minahas Utara - Ontorael, Jongli; Kapantow, Gene Henfried Meyer; Rumagit, Grace Adonia Josephine (AGRI-SOSIOEKONOMI, 2023)
The purpose of the study was to analyze the income of coconut farmers in Talawaan Village, Talawaan District, North Minahasa Regency. The research was conducted for 2 months, namely October to November 2022, starting from preparation to preparation of research reports. The research was conducted in Talawaan Village, Talawaan District, North Minahasa Regency. The data used in this study consisted of primary data and secondary data. Primary data is the result of direct interviews with respondent farmers using a questionnaire. Secondary data is complementary raw data obtained from agencies or offices related to the research site. Respondents in this study were coconut farmers in Talawaan Village, Talawaan District, North Minahasa Regency. Sampling in this study used a purposive method from 195 coconut farmers who were taken 30 coconut farmer respondents in Talawaan Village who were taken laterally. Data were analyzed using the calculation of farm income. The results showed that the income of coconut farmers in Talawaan Village, Talawaan Subdistrict, North Minahasa Regency for one copra production process was IDR 766,588 per farmer or IDR 403,467.77 per hectare.